The payment of interest in the financial system and the affection of the legal regulation of users of consumer credits - Mendoza García, Carlos Esmith (2016)
The present article deals with interest payment and its link with the consumption credits users guidance in Peru. Peruvian legislation regulates different legal regimes, for people outside the financial system, establishing limits in the interest agreement and also for the National System Enterprises that have a preferential treatment, as they are empowered to negotiate interests without being subject to maximum top amounts. This last regulatory regime is in disagreement with the consumption credits users protection because they don't take into account the evident disadvantages in which are such users; the regimen mentioned above leads to excessive interest rates, generating imbalance in the benefits derived from the contracts and the legitimization of the bad faith in the financial system commercial practices.